The Co-catalyst Effects of Mn(II), Zn(II), and Cr(III) Chlorides on Acidic Ionic Liquid Catalyzed Synthesis of Value-added Products from Cellulose in Aqueous Ethanol - Amarasekara, Ananda S.; Wiredu, Bernard; Animashaun, Moriam (Current Catalysis, 2023)
Background: Catalytic depolymerization and processing of cellulose can be used to produce value-added renewable feedstock chemicals. Objective: This study aimed to develop an acidic ionic liquid-metal ion chloride catalyst system-based single-reactor method for processing cellulose into value-added products. Methods: The effect of metal chlorides as co-catalysts on 1-(1-propylsulfonic)-3-methylimidazolium chloride acidic ionic liquid catalyzed degradation of cellulose in 40% (v/v) aq. ethanol was studied by measuring levulinic acid, ethyl levulinate, and 5-hydroxymethylfurfural yields. Results: In experiments with Mn(II) and Zn(II) chloride co-catalysts at 160 and 170°C for 12 h, the initial yields of ethyl levulinate and 5-hydroxymethylfurfural improved from 7% to 12-15% due to co-catalytic effects. The highest enhancements in ethyl levulinate yields were observed with CrCl3, where the yield increased from 6 to 27% with the addition of a 10 mol% co-catalyst. Conclusion: All three transition metal chlorides studied caused improvements in yields of secondary products, ethyl levulinate and 5-hydroxymethylfurfural, in acidic ionic liquid catalyzed degradation of cellulose in aqueous ethanol. The most significant enhancements in ethyl levulinate yields were observed with CrCl3 as a co-catalyst.
Keywords: ethyl levulinate